2014
DOI: 10.1371/journal.pone.0092795
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Liver Stiffness Value Using Transient Elastography during the Perioperative Period in Patients with Valvular Heart Disease

Abstract: Background/AimsLiver congestion due to heart failure in patients with valvular heart disease (VHD) can result in an overestimate of the liver stiffness (LS) as assessed by transient elastography (TE). This prospective pilot study investigated the dynamics of LS during the perioperative valve operation period.MethodsThirty-two patients who underwent a valve operation (case) and 12 who underwent a varicose vein operation (control) were prospectively enrolled. LS and cardiologic parameters at three time points [b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Baseline median LS was lower and within normal ranges in our population (5 kPa) compared with these articles 9 10. This is likely due to the difference of age distribution between the two populations—our patients tend to be younger with preserved cardiac function—even if the relationship between LS and age remains controversial 16 19.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Baseline median LS was lower and within normal ranges in our population (5 kPa) compared with these articles 9 10. This is likely due to the difference of age distribution between the two populations—our patients tend to be younger with preserved cardiac function—even if the relationship between LS and age remains controversial 16 19.…”
Section: Discussionmentioning
confidence: 55%
“…Other than Millonig et al ,8 Chon et al 9 investigated the dynamics of LS during the perioperative period after valvular heart surgery in 32 adult patients. They showed that LS could be dynamically reversed during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…7 Several groups have examined the effect of HF on the liver. [16][17][18] In a clinical study, LS measured by TE increased in patients with HF, and inter- Values are expressed as median (interquartile range), or n (%). A, late transmitral flow velocity; a', septal mitral annular late diastolic velocity; E, early transmitral flow velocity; e', septal mitral annular early diastolic velocity; E/e', ratio of peak mitral E wave velocity to peak early diastolic myocardial velocity at septal position recorded by tissue Doppler imaging; IVC, inferior vena cava; LAd, left atrial diameter; LVDd, left ventricular end-diastolic diameter; LVDs, left ventricular end-systolic diameter; LVEF, left ventricular ejection fraction; MR, mitral regurgitation; RAP, right atrial pressure; RVDd, right ventricular end-diastolic diameter; TAPSE, tricuspid annular plane systolic excursion; TR, tricuspid regurgitation; TRPG, tricuspid regurgitation pressure gradient.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is well demonstrated in a prospective study of 32 patients with valvular heart disease who underwent TE before and after valvular repair. Ninety days postoperatively, patients demonstrated a significant decline in liver stiffness (from 8.4 to 6.0 kPa, P = 0.026), suggesting improvement in congestion rather than reversal of fibrosis given the short time frame …”
Section: Noninvasive Biomarkers: Can We Estimate Liver Fibrosis In Comentioning
confidence: 99%
“…Ninety days postoperatively, patients demonstrated a significant decline in liver stiffness (from 8.4 to 6.0 kPa, P = 0.026), suggesting improvement in congestion rather than reversal of fibrosis given the short time frame. (30) Only one small study (n = 10) exists comparing liver stiffness determined by TE to fibrosis stage by biopsy, and no studies exist for ARFI. In the TE study, liver stiffness values overestimated the amount of fibrosis by at least one stage in 7 out of 10 subjects and overestimated the level of fibrosis by at least two stages in 5 out of 10 subjects.…”
Section: Imaging Modalities and Liver Stiffness Assessment Toolsmentioning
confidence: 99%